AL-QUR’AN WA AL-DIRASAH AL-IQTISADIYAH: AL-AZMAH FI LIBYA WA MU’ALAJATUHA HASB NADZARIYAH SAYYIDINA YUSUF AS - Saham Muhammad al-Maghadmi; JM Muslimin; Lathaif M Ghazali (Islam Futura, 2021)
The study aims to describe the plan and solution for economic crisis in the era of Prophet Yusuf and to find out how the economic crisis in Libya was and the implementation of the plan in order to solve Libyan economic crisis. The researcher employed descriptive analysis as the research method. The data were collected using scientific documents and interviews. The study result shows that economic crisis in the era of Prophet Yusuf included fifteen years of food crisis and the budget planning consisted of three stages namely: early warning stage and the preparation for the crisis called as the seven first phase and phase facing the crisis called as the seven second phase and the reactivity phase is called as annual cycle. The Libyan economic crisis was due to the decrease of its macroeconomy and the weak condition of state institutions leading to significant oil production decrease and the shutdown of the harbors, the increase of the unemployed due to drastic decrease of non-oil sector, liquidity in financial sector without state assistance further weakened Libyan economy both in the trade and industrial activities contributing to high inflation. The implementation of resolution for Libyan economic crisis: the use of agricultural cycle strategy, budget planning strategy, production distribution strategy using legalization knowledge, limited speculation, the planning of social relationship and price stabilization